ANALISIS KEBERHASILAN REVEGETASI PASCA TAMBANG BATUBARA DI PD. BARAMARTA KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Ahmad Rizal; Kissinger Kissinger; Syam’ani Syam’ani (Jurnal Sylva Scienteae, 2020)
The implementation of mining activities often causes environmental damage so it must be followed by reclamation and revegetation activities. The purpose of this study is to analyze the success of post-coal revegetation based on the percentage aspects of plant growth, species diversity, percentage of health, tree diameter and height and increment in PD. Baramarta Banjar Regency, South Kalimantan Province.The data collected is primary taken from plots of 10 mx 50 m, the main stand were measured by se veral plots that size10 mx 10 m, of sampling were measured in plot size 5 mx 5 m, natural plants seedling and understorey were measured in plot size 2 mx 2 m, the secondary data were collected from institution of stake holder.The highest growth percentage of the five research plots based on planting years was in 2014 (100%), plot  2016 (90.32%) and plot 2017 (100%). Conecluded that the revegetation succes are very good because its succes were above 90%, the diversity of understorey in reclamatation land is still low, especially for the sampling level while seedling levels are not found on the land, plants in the five research plots are classified as healthy because 4 out of 5 plots measured the healthy percentage of plants over 90%, increment of diameter and height of sengon laut trees and sengon buto is higher than the type of acacia, tread of diameter and height revegetation relative better than first year after planting and decreasing with getting older age of plantsKeywords: Postmining; revegetation; reclamation; diversity of types; percentage growing; percentage of health